2011
DOI: 10.1093/nar/gkr206
|View full text |Cite
|
Sign up to set email alerts
|

An RNA aptamer perturbs heat shock transcription factor activity in Drosophila melanogaster

Abstract: Heat shock transcription factor (HSF1) is a conserved master regulator that orchestrates the protection of normal cells from stress. However, HSF1 also protects abnormal cells and is required for carcinogenesis. Here, we generate an highly specific RNA aptamer (iaRNAHSF1) that binds Drosophila HSF1 and inhibits HSF1 binding to DNA. In Drosophila animals, iaRNAHSF1 reduces normal Hsp83 levels and promotes developmental abnormalities, mimicking the spectrum of phenotypes that occur when Hsp83 activity is reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 52 publications
0
25
0
1
Order By: Relevance
“…In contrast, D01 RNA showed a typical binding curve with a dissociation constant ( K d ) of 273 (± 29) n m . This K d value is one‐two order higher than those of the previously reported RNA aptamers that inhibit intracellular DNA‐binding proteins (discussed below).…”
Section: Resultsmentioning
confidence: 65%
“…In contrast, D01 RNA showed a typical binding curve with a dissociation constant ( K d ) of 273 (± 29) n m . This K d value is one‐two order higher than those of the previously reported RNA aptamers that inhibit intracellular DNA‐binding proteins (discussed below).…”
Section: Resultsmentioning
confidence: 65%
“…This allows HSF1 to form trimers and translocate to the cell nucleus and activate transcription [7]. Its function is not only critical to overcome the proteotoxic effects of thermal stress, but also needed for proper animal development and the overall survival of cancer cells [100, 101]. It is worth mentioning that we have previously shown a synergistic effects of TSC1 as a neuroprotective agent.…”
mentioning
confidence: 99%
“…The Drosophila MAPK pathway was previously reported by us to be affected by the HSF1 aptamer [14]. Likewise, the Lindquist and Gius Laboratories have demonstrated that HSF1 depletion also affect this pathway [22]–[23], [25].…”
Section: Resultsmentioning
confidence: 90%